2018
DOI: 10.1186/s12913-018-2908-1
|View full text |Cite
|
Sign up to set email alerts
|

Active listing and more consultations in primary care are associated with reduced hospitalisation in a Swedish population

Abstract: BackgroundHealthcare systems are complex networks where relationships affect outcomes. The importance of primary care increases while health care acknowledges multimorbidity, the impact of combinations of different diseases in one person. Active listing and consultations in primary care could be used as proxies of the relationships between patients and primary care. Our objective was to study hospitalisation as an outcome of primary care, exploring the associations with active listing, number of consultations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Studies on predictors of high quality primary care have also stated that longer consultations and good teamwork are important for quality of care [28,29]. Previously we have studied mean days hospitalised as an outcome of primary care, accounting for socioeconomic factors also analysing difference between primary care practices [25]. Both our studies show that active listing and more than mean consultations in primary care lower mean days hospitalised, adjusting for morbidity burden.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies on predictors of high quality primary care have also stated that longer consultations and good teamwork are important for quality of care [28,29]. Previously we have studied mean days hospitalised as an outcome of primary care, accounting for socioeconomic factors also analysing difference between primary care practices [25]. Both our studies show that active listing and more than mean consultations in primary care lower mean days hospitalised, adjusting for morbidity burden.…”
Section: Discussionmentioning
confidence: 53%
“…Our use of a coherent Swedish healthcare system tried to control for such factors. Mean days hospitalised and relationships with primary care have recently been studied for this population accounting for socioeconomic factors [25] showing decreasing mean days hospitalised with active listing and more consultations in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Swedish study, the result showed that active patient -doctor listing and more consultations in primary care are associated with reduced mean days hospitalised, when adjusting for socioeconomic status and multimorbidity level. In conclusion, the promotion of well performing primary care is worthwile to maintain good relationships with patients and possibly reduce mean days hospitalised (48). The risk of hospitalisation is increased in relation to morbidity burden and is therefore of particular interest in relation to elderly patients and individuals with cognitive impairment.…”
Section: Brief History Of Swedish Primary Health Carementioning
confidence: 99%
“…NCDs' [12, p.4-5]. Comparative studies have shown that strong primary care systems achieve better health outcomes and better results in relation to both cost-containment and reducing inequality in access to, and accessibility of, care; they also support more effective service utilisation elsewhere in the health system [3][4][13][14][15][16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sweden is also committed to an integrated and people-centred model of primary care with some gatekeeping. Care is usually provided by multi-professional teams in larger centres, but there is variation between the different Counties and between the urban and remote (especially Arctic) areas [16,40].…”
Section: Accepted Manuscriptmentioning
confidence: 99%